Shareholder value and the common good : essays on the objectives and purposes of business management - Lutz, David; Mimbi, Paul (Strathmore University, 2005)
What is the objective or purpose of business Management? According to the dominant theory of contemporary financial management scholarship, agency theory, business managers are obligated to maximise owner or shareholder value. According to most theories of business ethics, however, some owner-value-maximising actions should not be performed, because they would be unethical. Because business management scholars and business ethics scholars have not resolved this contradiction, students of commerce receive a contradictory education. The twenty-five essays in this interdisciplinary, international.